Quantitative In-Situ NMR Illumination for Excitation and Kinetic Analysis of Molecular Motor Intermediates - Wilcken, Roland; Gerwien, Aaron; Huber, Ludwig Alexander; Dube, Henry; Riedle, Eberhard (Chemphotochem, 2022)
Modern synthetic methods can be highly complex and proceed via multiple sequential processes. The intricate concepts can rarely be checked in all necessary detail due to the lack of suitable analysis methods. For photoinitiated reactions the starting point can be chosen to any desired precision by short or ultrafast light pulses. However, the optical analysis is blind to many aspects. Pairing the illumination of the reaction mixture with other online detection schemes proves extremely valuable. Herein we present a combination of variable temperature NMR spectroscopy with in-situ illumination and photon-counting to monitor the short-lived intermediates and gain a comprehensive and quantitative picture of the working of a hemithioindigo-based molecular motor. Application of the scheme is not limited to the field of molecular machines, we rather think that it will be of great use for any detailed identification and characterization of chemical intermediates in photochemistry, photoredox catalysis, photoswitching, or photoresponsive materials.
CRIS-Team WoS Importer:2022-01-21